Rectal Administration of Ibuprofen: Comparison of Enema and Suppository Form - Prasaja, Budi; Harahap, Yahdiana; Sandra, Monika; Iskandar, Irene; Lusthom, Windy; Cahyaningsih, Prawitasari (Drug Research, 2021)
Ibuprofen is a widely used and well-tolerated analgesic and antipyretic. It is desirable to have a formulation with a rapid rate of absorption because it is required for rapid pain relief and temperature reduction. Previous studies have described the pharmacokinetic profiles of ibuprofen suppository and the mean peak times of ibuprofen suppository were around 1.8 hours, indicating a slower rate of absorption. The aim of this study is to compare the pharmacokinetic parameters of rectal administration of ibuprofen between enema and suppository form in order to provide evidence for the faster absorption rates of ibuprofen enema. This study was a phase-1 clinical study, open-label, randomized and two-way crossover with one-week washout period comparing the absorption profile of equal dose of ibuprofen administered rectally in two treatment phases: ibuprofen suppository and enema. Blood samples were collected post dose for pharmacokinetic analyses. Tmax was analyzed using a Wilcoxon matched paired test. A standard ANOVA model, appropriate for bioequivalence studies was used and ratios of 90% confidence intervals were calculated. This study showed that Tmax for ibuprofen enema was less than half that of ibuprofen suppository (median 40 min vs. 90 min, respectively; p-value=0.0003). Cmax and AUC0–12 for ibuprofen enema were bioequivalent to ibuprofen suppository, as the ratio of test/reference=104.52%, 90% CI 93.41–116.95% and the ratio of test/reference=98.12%, 90%CI 93.34–103.16%, respectively, which fell within 80–125% bioequivalence limit. The overall extent of absorption was similar to the both, which were all well tolerated. In terms of Tmax, Ibuprofen enema was absorbed twice as quickly as from ibuprofen suppository. Therefore it is expected that an ibuprofen enema may provide faster onset of analgesic and antipyretic benefit.
Keywords: enema; fever; ibuprofen; rectal